Nickel nanoparticles: a highly efficient and retrievable catalyst for the solventless Friedlander annulation of quinolines and their in silico molecular docking studies as histone deacetylase inhibitors1. Issue 57 (25th June 2015) - Angajala, Gangadhara; Subashini, Radhakrishnan
<x xml:space="preserve">Abstract</x> Highly efficient, solvent-free protocol for the synthesis of polysubstituted quinolines via Friedlander annulation using nickel nanoparticles from Aegle Marmelos Correa aqueous leaf extract.